Relationship between physical function and biomechanical gait patterns in boys with haemophilia. (26th October 2016) - Stephensen, D.; Taylor, S.; Bladen, M.; Drechsler, W. I.
Abstract : Introduction: The World Federation of Haemophilia recommends joint and muscle health is evaluated using X‐ray and magnetic resonance imaging, together with clinical examination scores. To date, inclusion of performance‐based functional activities to monitor children with the condition has received little attention. Aim: To evaluate test–retest repeatability of physical function tests and quantify relationships between physical function, lower limb muscle strength and gait patterns in young boys with haemophilia. Methods: Timed 6‐minute walk, timed up and down stairs, timed single leg stance, muscle strength of the knee extensors, ankle dorsi and plantar flexors, together with joint biomechanics during level walking were collected from 21 boys aged 6–12 years with severe haemophilia. Results: Measures of physical function and recording of muscle strength with a hand‐held myometer were repeatable (ICC > 0.78). Distances walked in six minutes, time taken to go up and down a flight of stairs and lower limb muscle strength correlated closely with ankle range of motion, together with peak knee flexion and ankle dorsi and plantarflexion moments during walking ( P < 0.05). Conclusion: Alterations in gait patterns of boys with haemophilia appear to be associated with changes in performance of physical function and performance seems to depend on their muscle strength. Timed 6‐minute walk test, timed up and down steps test and muscle strength of the knee extensors showed the strongest correlation with biomechanical joint function, and hence might serve as a basis for the clinical monitoring of physical function outcomes in children with haemophilia.